Phonological Error in Korean Plosives by Indonesian Learners: A Generative Phonology Approach - Azzahra, Adinda Ayu; Subiyanto, Agus (Journal of Language and Literature Studies, 2026)
This study examines the Korean plosives phonological errors uttered by self-taught Korean language learners from Indonesia who have Javanese as their L1. This study reveal systematic difficulties learners face in perceiving and producing target-language sounds that often influenced by their first language. Analyzing these errors helps explain developmental patterns in pronunciation learning and informs effective teaching strategies. This study uses a qualitative descriptive approach and uses distinctive features by Schane (1973) from generative phonology transformational theory to identify the phonological process that happened in those errors and explain speech sounds using systematic features. The data from this study is collected from observing the pronunciation of fifteen Korean language learners through video calls by providing them texts to read in hangeul (the Korean writing system). We recorded the data, transcribed the phonetic transcriptions, analyzed and classified the phonological processes, discovered, and concluded the analysis. As a result, the findings show that learners produced twenty Korean plosives errors. These errors can be grouped into three main phonological processes, all of which are influenced by interference from Javanese phonology. This findings suggest that Korean pronunciation teaching for Indonesian learners should focus more on plosives and deal with the influence of the first language.